Teacher competency, facilities, and motivation as drivers of vocational graduate work readiness: a PLS-SEM moderation analysis - Andri Dermawan; Lasyatta Syaifullah; Deded Darmadi; Muhammad Anwar; Wakhinuddin Simatupang (Journal of Counseling, Education and Society, 2026)
Vocational education programs in Indonesia face persistent structural misalignment between graduate competencies and industry demands, reflected in the vocational high school graduate unemployment rate of 9.84% despite enrollment of 5.08 million students. This study examined the effects of Teacher Competency (X1), Learning Facilities (X2), and Student Motivation (X3) on Student Work Readiness (Y), the mediating role of Student Motivation, and the moderating and direct effects of Industry Relevance (M). A quantitative explanatory survey design was employed with total sampling involving 350 students at vocational high schools in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. All seven hypotheses were supported: Teacher Competency (β = 0.207, p = 0.000) and Learning Facilities (β = 0.211, p = 0.000) significantly predicted Student Motivation; Teacher Competency (β = 0.223), Learning Facilities (β = 0.270), and Student Motivation (β = 0.246) exerted significant direct effects on Work Readiness; Student Motivation mediated X1→X3→Y (β = 0.051) and X2→X3→Y (β = 0.052); Industry Relevance moderated Learning Facilities and Work Readiness (β = 0.151, p = 0.001); and Industry Relevance exerted a significant negative direct effect on self-assessed Work Readiness (β = −0.167, p = 0.001), interpreted as a perception gap mechanism. R² = 0.280 for Student Work Readiness. These findings provide evidence-based guidance for policymakers and school leaders to improve vocational education quality and graduate employability in Indonesia.